PEMODELAN SPASIAL EPIDEMIOLOGI DEMAM BERDARAH DENGUE MENGGUNAKAN SISTEM INFORMASI GEOGRAFI DI KECAMATAN DEPOK KABUPATEN SLEMAN YOGYAKARTA - Widayani, Prima (Jurnal Pendidikan Geografi Gea, 2010)
The objective of this research is for developing a prototype of Dengue Haemorrhagic Fever Epidemiologic Spatial Modeling to define the irritable area rates for that disease. The research is conducted at Depok, Sleman, Yogyakarta.Â  The modelâs made by GIS with overlaying 8 parameters: population density, the cleaning activity frequency of water vessel, waste management pattern, frequency of fogging, drainage condition, settlement pattern, distance settlement from river, and survillance. Each parameterâs analyzed by cross tabs analyze to see its correlation with the actual case.Â  The result from this analyze is used to give weighting factors for those parameters. The research finding show that 8 parameters have partial correlation with actual case of dengue fever. The result model is tested again with the actual dengue fever case.Â  As we can see from crosstab test ,the value of C (coefficient contingency) = 0,558.Â  So the research gives a meaningful test, and we can take conclusion that thereâs a real correlation between dengue fever irritable model and actual dengue fever case.